2014
DOI: 10.1186/1471-2164-15-680
|View full text |Cite
|
Sign up to set email alerts
|

Expression quantitative trait loci infer the regulation of isoflavone accumulation in soybean (Glycine max L. Merr.) seed

Abstract: BackgroundMapping expression quantitative trait loci (eQTL) of targeted genes represents a powerful and widely adopted approach to identify putative regulatory variants. Linking regulation differences to specific genes might assist in the identification of networks and interactions. The objective of this study is to identify eQTL underlying expression of four gene families encoding isoflavone synthetic enzymes involved in the phenylpropanoid pathway, which are phenylalanine ammonia-lyase (PAL; EC 4.3.1.5), cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 78 publications
2
28
0
Order By: Relevance
“…Since, biochemical pathways and enzyme protein sequences are known for some of seed composition traits, candidate gene identification is much easier for these traits resulting in the development of several functional markers in soybean i.e., oleic acid content, isoflavone content, and raffinose content etc. (Dierking and Bilyeu, 2010; Pham et al, 2010, 2011; Wang et al, 2014). However, for agronomic and yield related traits, biochemical pathways are not well-characterized and therefore QTL mapping is the major strategy for identification of underlying genes.…”
Section: Difficulties Challenges and Potential Errors In Qtlomics Amentioning
confidence: 98%
See 3 more Smart Citations
“…Since, biochemical pathways and enzyme protein sequences are known for some of seed composition traits, candidate gene identification is much easier for these traits resulting in the development of several functional markers in soybean i.e., oleic acid content, isoflavone content, and raffinose content etc. (Dierking and Bilyeu, 2010; Pham et al, 2010, 2011; Wang et al, 2014). However, for agronomic and yield related traits, biochemical pathways are not well-characterized and therefore QTL mapping is the major strategy for identification of underlying genes.…”
Section: Difficulties Challenges and Potential Errors In Qtlomics Amentioning
confidence: 98%
“…In soybean, isoflavones are critical factor in defense against pathogens (Benhamou and Nicole, 1999; Subramanian et al, 2004), in promoting nodulation by rhizobia (Subramanian et al, 2006, 2007) and in changing or adjusting the microbial population around plant roots (Lozovaya et al, 2004). Several QTLs have been mapped for three species of isoflavones i.e., genistein ( GEN ), daidzein ( DAI ), glycitein ( GLY ), and total of isoflavones ( TOT ) (Primomo et al, 2005; Zeng et al, 2009; Gutierrez-Gonzalez et al, 2010, 2011; Wang et al, 2014). Gutierrez-Gonzalez et al (2010, 2011) identified and validated a major QTL in two RILs derived from low isoflavone lines Magellan and Essex, and high isoflavone line PI 437654.…”
Section: Qtlomics: Qtls To Genes In Soybeanmentioning
confidence: 99%
See 2 more Smart Citations
“…, Wang et al. ). However, conventional QTL analysis methods could not show the actions of these genes directly.…”
mentioning
confidence: 99%